Androgen receptor variant 12 promotes migration and invasion by regulating MYLK in gastric cancer. Issue 3 (10th April 2019) - Xia, Nan; Cui, Jiantao; Zhu, Min; Xing, Rui; Lu, Youyong
Abstract: Androgen receptor (AR) and its variants (AR‐Vs) promote tumorigenesis and metastasis in many hormone‐related cancers, such as breast, prostate and hepatocellular cancers. However, the expression patterns and underlying molecular mechanisms of AR in gastric cancer (GC) are not fully understood. This study aimed to detect the expression of AR‐Vs in GC and explored their role in metastasis of GC. Here, the AR expression form was identified in GC cell lines and tissues by RT‐PCR and qPCR. Transwell assays and experimental lung metastasis animal models were used to assess the function of AR in cell migration and invasion. Downstream targets of AR were screened by bioinformatics, and identified by luciferase reporter assays and electrophoretic mobility shift assays. AR‐v12 was identified as the main expression form in GC cell lines and tissues. Different from full length of AR, AR‐v12 was localized to the nucleus independent of androgen. Upregulation of AR‐v12 in primary GC tissues was significantly associated with metastasis. Overexpression of AR‐v12 promoted migration and invasion independent of androgen. Knockdown of AR‐v12 inhibited migration and invasion in vitro, as well as metastasis in vivo . Furthermore, AR‐v12, serving as a transcription factor, promoted metastasis through regulating the promoter activity of MYLK. In AR‐v12 overexpressing cells, knockdown of MYLK inhibited cell migration and invasion, while in AR‐v12 knocked‐down cells, overexpression of MYLK promoted cell migration and invasion. Collectively, our study demonstrates that AR‐v12 is highly expressed in GC tissues and promotes migration and invasion through directly regulating MYLK. Copyright © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.